A Case of Alpha-1 Antitrypsin Deficiency and Organizing Pneumonia - Renduchintala, Kavita (Cureus, 2020)
Alpha-1 antitrypsin deficiency (AATD) is an autosomal dominant genetic disorder that presents with pulmonary complications and is most commonly manifested by panacinar emphysema and chronic obstructive pulmonary disease. A 49-year-old Caucasian female with a history of AATD and chronic tobacco use was referred to both infectious disease and thoracic surgery clinics with worsening cough and chronic intermittent hemoptysis for the evaluation of possible superimposed infection or malignancy. She had previously been treated with multiple antibiotics and Prolastin-CÒ (alpha-1-proteinase inhibitor). Initial CT of the chest showed known chronic bronchiectasis, severe lower lung emphysema, and right-sided lower lobe pulmonary masses. CT-guided biopsy of one mass showed nonspecific inflammation, negative cultures, and negative cytology. Subsequent follow-up with chest CT scans showed a decreasing size of right-sided pulmonary masses and new left-sided nodule formation, which later stabilized in growth. Based on symptoms and radiological and pathological findings, a diagnosis of organizing pneumonia was made. We present an unusual case of bilateral pulmonary masses mimicking infection and malignancy later found to be most consistent with an organizing pneumonia in a patient with underlying AATD.